Computing in evolution-communication P systems with energy - Juayong, Richelle Ann B.
Due to the limitations of today's standard computers, the natural computing paradigm introduces biologically-inspired computational models and techniques in order to device new ways of computing. A relatively new branch of the natural computing paradigm called membrane computing abstracts features and functions occuring on living cells. The theoretical model used for the membrane computing is called a P-system. In this work we are particularly interested in a specific variant of P system called Evolution-Communication P system with energy (ECPe system) which was introduced in 2009 to initiate communication complexity in the domain of P systems. We take part in the analysis of ECPe system?s computation by exploring its computational power and matrix representation. Specifically, we improve previous universality results of ECPe systems by incorporating rules that are similar to the antiport process of transporting molecules in cells. We also investigate the use of dynamical communication measures derived from computations on ECPe systems in examining the quality of communication through so-called Sevilla carpets. Finally, we represent computations in ECPe systems as matrix operations and answer the problem of computing forward and backward by extending previous works in other P system variants. Our motivation is the use of algebraic representation in analyzing computations in ECPs systems as proven in other types of P system and the possible simulation of ECPe systems computations in parallel processors, specifically, in Graphical Processing Units (GPUs).